(untitled) (Research, Society and Development, 2025)
Proper nutrition is one of the main factors influencing reproductive efficiency in female cattle, directly affecting pregnancy rates and the sustainability of livestock production. This study aimed to review scientific literature on the relationship between nutrition and bovine fertility, highlighting the effects of energy balance, proteins, vitamins, and minerals on conception and pregnancy maintenance. The results indicate that mineral supplementation, especially with phosphorus, zinc, and selenium, plays a key role in ovarian function and oocyte quality, while deficient diets increase the occurrence of anestrus, embryonic losses, and longer calving intervals. It is concluded that well-structured nutritional programs contribute to higher pregnancy rates, improved profitability in livestock systems, and greater sustainability in production.